AKTIVITAS ANTIHIPERGLIKEMIK DARI EKSTRAK ETANOL DAN n-HEKSANA DAUN KEMBANG BULAN [Tithonia diversifolia A.Gray] PADA TIKUS PUTIH JANTAN - Ary Rizki Darmawi; Chairul Saleh; Rudi Kartika (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
Phytochemical test and antihyperglicemic activity from ethanol extract dan n-hexane extract from kembang bulan (Tithonia diversifolia A.Gray) leaf has been carried out. Based on the test result of phytochemistry of secondary metabolites compounds from kembang bulan (Tithonia diversifolia A.Gray) leaf showed that ethanol extract fraction containing flavonoid, fenolik, alkaloid and saponin. Whereas at n-hexane extract fraction containing alkaloid, saponin and steroid. Antihyperglicemic activity test using the method of glucose tolerance where a white male rats got induced by sucrose. Measurement of blood sugar levels using glucometer and glucose test strip. From this test shows that the most active fractions to reduce blood sugar levels was ethanol extract with a dose of 77 mg/kg BB with percentage of blood sugar levels reduction in the amount of 54.15 % it was close with reduction percentage from acarbose as positive control in the amount of 55.57 %.